The yeast 14-3-3 proteins Bmh1 and Bmh2 regulate key signaling pathways - Obsilova, Veronika; Obsil, Tomas (Frontiers in Molecular Biosciences, 2024)
Cell signaling regulates several physiological processes by receiving, processing, and transmitting signals between the extracellular and intracellular environments. In signal transduction, phosphorylation is a crucial effector as the most common posttranslational modification. Selectively recognizing specific phosphorylated motifs of target proteins and modulating their functions through binding interactions, the yeast 14-3-3 proteins Bmh1 and Bmh2 are involved in catabolite repression, carbon metabolism, endocytosis, and mitochondrial retrograde signaling, among other key cellular processes. These conserved scaffolding molecules also mediate crosstalk between ubiquitination and phosphorylation, the spatiotemporal control of meiosis, and the activity of ion transporters Trk1 and Nha1. In humans, deregulation of analogous processes triggers the development of serious diseases, such as diabetes, cancer, viral infections, microbial conditions and neuronal and age-related diseases. Accordingly, the aim of this review article is to provide a brief overview of the latest findings on the functions of yeast 14-3-3 proteins, focusing on their role in modulating the aforementioned processes.